Effect of Astragalus eremophilus on the Growth of Bracharia ramose - Muhammad Nadeem Khan; Mushtaq Ahmad; Rahmat Ali Khan; Nadia Mushtaq; Muhammad Wasim Khan; Mir Sadiq Shah; Muhammad Nisar Ul Haq (Journal of Basic & Applied Sciences, 2017)
Astragalus eremophilus is traditionally used as a potent antimicrobial, anti-inflammatory and antioxidant medicinal plant. In the present study we proposed to assess an allelopathic property of the aqueous extract of Astragalus eremophilus. Proposed plant of Astragalus eremophilus was collected from the catchment area of University of Science and Technology Bannu in its growing season. The plant parts were dried in shed, grounded to powdered form and saturated with de-ionized water to prepare aqueous crude extract. Promising effects were shown by the crude aqueous extract of Astragalus eremophilus (root and stalk) growth control and least stalk development at high concentration with respect to control. The effect of Astragalus eremophilus on roots and stalk development of Bracharia ramose is as follows; 40% > 30% > 20% > 10%. Astragalus eremophilus could be used as an alternative for weed control as evident by the present study, where further characterization studies are recommended for the production of plant based natural herbicides.